Transformador de estado sólido CA-CC com estágio integrado baseado no cascateamento e intercalamento de conversores ponte completa para aplicação em trens elétricos - Pacheco, Juliano de Oliveira (2019)
Solid state transformers are gaining more prominence today due to the increased use of renewable energies, smart grids and systems that require weight and volume reduction as applications in electric traction. Thus, this thesis proposes the study and development of a single stage biderectional AC-DC converter topology based on the multilevel modular converter. This topology is based on the modular multilevel converter and employs the concepts of interleaving converters and integrating power stages. This topology has the presence of three magnetic elements, which are a transformer that ensures galvanic isolation at high frequency, an input current filter inductor and an inductor to aid in the transfer of power from the primary to the secondary side of the converter. The main characteristics of the structure come from the concepts employed, such as passive elements operating with an effective frequency higher than that of switching, minimizing current ripples in medium frequency and reduced volume and weight. A qualitative analysis is carried out, showing the operation steps of the converter, the modulation technique used, as well as the control strategy adopted for the converter. Quantitative analysis is also performed showing the converter's loss calculations, the variation of the input current and the power flow analysis between the primary and secondary of the converter. The controllers are dimensioned in the discrete domain and in the frequency domain. Finally, the simulation and experimental results of the converter are presented, operating with a switching frequency of 5 kHz, nominal power of 1.5 kW, output voltage of 300 V and supply voltage of 165 V with a frequency of 60 Hz. A high power factor, around 0.99, a low harmonic distortion of the input current of 3.6%, and a efficiency of 87% were achieved.